Effect of air abrasion treatment on microleakage of a pit and fissure sealant (in vitro study) (Mustansiria Dental Journal, 2018)
The aim of this study was to compare in vitro the microleakage of a pit and fissuresealant after different enamel surface treatments: (1) acid etching only, (2) airabrasion only, and (3) air abrasion followed by acid etching.Thirty sound human upper premolars were used in this study. The teeth weredivided into three groups according to the type of treatment prior to sealantapplication: Group 1 (in which the occlusal surface was etched with 37% phosphoricacid gel for 30 seconds), Group 2 (in which the occlusal surface was air-abraded for10 seconds with sodium hydrogen carbonate powder), and Group 3 (in which theocclusal surface was air-abraded as in group 2 and then acid etched as in group 1).Then a light-cured pit and fissure sealant (Fisseal, Promedica, Germany) was appliedto the central fissure in the occlusal surface of each tooth and light cured for 20seconds. Then the teeth were thermocycled between 5ºC and 55ºC for 10 cycles,immersed in 0.5% basic fuchsine dye for 24 hours at room temperature, embedded inauto-polymerizing acrylic resin, sectioned longitudinally bucco-lingually, andexamined under a stereomicroscope for dye penetration.The results of this study showed that the highest mean of microleakage scores wasin group 2 (air abrasion group), while the lowest mean of microleakage scores was ingroup 3 (air abrasion + acid etching), with statistically highly significant difference(p0.05).Air abrasion treatment prior to sealant application was not effective in reducingmicroleakage and should be followed by acid etching.